A utilização de tecnologias digitais Open Source: uma contribuição ao estudo comparativo de ambientes virtuais na PUC-SP - Brigatti Junior, Luiz Antonio (2010)
Methods that allow the observation of users of virtual learning environments acting in the work place tend to become increasingly more necessary when the number of computer users and the inherent complexity of systems grow. Processes of continuous assessment carried out during the life cycle of Virtual Learning Environments (VLEs) seem to be required condition for users to reach good results. This research used information provided by professors to verify their usage process, and compare the use of the open source tools and the difficulties found in the virtual environments Moodle and TelEduc , both in use at PUC-SP. Thus, this dissertation argues that approaches in which VLEs are used by the faculty members of the School of Economics, Administration, Accounting and Actuary (FEA at PUC-SP) represent tools of effective gain in quality